Properties of massive stars before death - Allan, Andrew (Trinity College Dublin. School of Physics. Discipline of Physics, 2021)
Despite their importance, there is a lot yet to be learned regarding massive stars, particularly those at late evolutionary stages. In the first of two studies presented here, we investigate a suspected very massive star in one of the most metal-poor dwarf galaxies, PHL 293B. Excitingly, we report the disappearance of signatures previously associated with a massive Luminous Blue Variable (LBV) from our two 2019 spectra, in particular, broad Balmer emission with prominent P-Cygni profiles. Using CMFGEN, we compute radiative transfer models to predict properties of the LBV. Our models show that during 2001-2011 the LBV had: a luminosity of 2.5-3.5x10^6 Lsun, a mass-loss rate of 0.005-0.020 Msun/yr, a wind velocity of 1000 km/s, effective and stellar temperatures of 6-6.8 kK and 9.5-15 kK, respectively. These properties indicate an eruptive state. We consider two main hypotheses for the absence of the broad emission components from the spectra obtained since 2011. One possibility is that we are seeing the end of an LBV eruption of a surviving star, with a mild drop in luminosity, a shift to hotter effective temperatures, and dust obscuration. Alternatively, the LBV could have collapsed to a massive black hole without the production of a bright supernova. The second study considers Type-Ibn supernovae (SNe). Their early-time spectra feature narrow emission lines of mostly He, signatures of interaction between SN ejecta and a dense, H-poor, He-rich circumstellar medium (CSM). Assuming this CSM was expelled by the progenitor prior to explosion, these signatures allow for predictions of progenitor properties such as mass-loss rate and surface composition. Hence, we fit CMFGEN models to early-time spectra of Type-Ibn SNe. It is our understanding that this will be the first detailed radiative transfer study for such spectra. Our best-fit models to a spectrum of SN 2010al obtained 5.7 days post explosion predict: a SN luminosity between 5.3-10x10^10 Lsun, a progenitor mass-loss rate between 0.34-0.52 Msun/yr, a wind velocity of 1000 km/s, an inner boundary radius to the CSM of 1.2x10^15 cm. These properties, combined with the H-free and N-rich nature of our models are consistent with the progenitor being H-stripped (probably of WN type), exploding as a Type-I SN surrounded by a dense H-free, He-rich CSM as suggested by Pastorello et al. (2015). We can also not rule out the explosion of a small-mass, stripped-envelope star surrounded by a He-rich CSM which could have been ejected by a binary interaction.
APPROVED
Keywords: Massive Stars; CSM-interacting supernovae; black holes; radiative transfer modelling